Theresimima ampellophaga (Bayle-Barelle, 1808) rediscovered in the Republic of North Macedonia by using sex attractant traps (Lepidoptera: Zygaenidae) - A. Nahirnic-Beshkova; S. Beshkov; E. E. Kucherenko; K. A. Efetov (SHILAP)
Theresimima ampellophaga (Bayle-Barelle, 1808) was known from only three sites in North Macedonia and has never been considered as a pest of grapevine in this territory. The last time it was recorded in North Macedonia about 80 years ago. Traps baited with synthetic sex attractant EFETOV-2 (racemic mixture of (2R)-butyl 2-dodecenoate and (2S)-butyl 2-dodecenoate) were set at two localities near Ohrid Lake at Trebenishta village and between Ljubanishta village and Sveti Naum Monastery in 2016, in Vardar river valley near Demir Kapija in 2017 and near Dojran Lake in 2018. In North Macedonia sex attractants were used for the detection of this species for the first time. We recorded Th. ampellophaga in traps at all four monitored localities.